Factors That Influence Financial Behaviour In Generation Z In Bengkulu City - Vettyca Diana Saputri; Karona Cahya Susena; Lydia Gustina Putri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine the factors that influence Financial Behaviour in generation Z Bengkulu City. The focus of this study is to determine whether Financial attitude, Financial Knowledge and Financial Self-Effivcacy affect fianancial behaviour in generation Z Bengkulu City. The approach used is a quantitative approach with primary data. The sample in this study were generation Z in Bengkulu city, namely 100 people. The result of the multiple linear regression analysis is the equation Y = 1.766 + 0.347 X1 + 0.321 X2 + 0, 479 X3 + e, this illustrates the positive direction of regression, meaning that the variables Financial Attitude, Financial Knowledge, Financial Self-Efficacy have a positive influence on Financial Behaviour (Y) in Generation Z Bengkulu City.From the results of calculations using SPSS 25, it can be seen that the coefficient of determination of R square is 0.593. This means that the value of financial attitide (x1), financial knowledge (x2) and financial self-efficacy (x3) affects Financial Behaviour (Y) by 59.3% while the remaining 40.7% is influenced by other variables not examined in this study. The results of the t test at the significance level <0.05 explain that partially financial attitide (x1), financial knowledge (x2) and financial self-efficacy have a significant effect on Financial Behaviour (Y) in Generation Z Bengkulu City. The results of the f test are smaller than 0.050, so the variables financial attitide (x1), financial knowledge (x2) and financial self-efficacy (x3) have a significant effect on Financial Behaviour (Y) in generation Z Bengkulu City.